The Therapeutic Engagement Questionnaire (TEQ): a service user-focused mental health nursing outcome metric - Chambers, Mary (BMC Psychiatry, 2019)
BACKGROUND: Therapeutic engagement (TE) has been described as the crux of mental health nursing but despite its perceived importance, to date, there is no measurement tool that captures it. As a result, there is no way of determining the contribution of mental health nursing interaction to service user recovery, in acute inpatient mental health settings or the wider care quality agenda. METHODS: To develop and validate a TE measurement tool in partnership with Service Users (SUs) and Registered Mental Health Nurses (RMHNs). The TEQ was developed in 3 stages: 1) item generation (and pre-testing), 2) item reduction using Principal Component Analysis (PCA), and 3) validation across Mental Health Trusts in England. RESULTS: The final questionnaire has two versions, (SU and RMHN version), each scored within two contexts (1–1 SU-RMHN interactions and overall environment and atmosphere of the ward) and includes 20 items with two sub-scales (care interactions and care delivery). Psychometric evaluation of the TEQ shows high inter-scale correlations (0.66–0.95 SU; 0.57–0.90 RMHN), sound sub-scale internal consistency (> 0.95), concurrent validity (> 0.60) and adequate score variability for both versions of the TEQ. In summary, the TEQ behaves well as a measurement tool. CONCLUSIONS: The TEQ can determine the collaborative and empathic nature of RMHN-SU interactions, capture if SUs are treated with dignity and respect and recognise that the principles of the recovery approach are being respected. The TEQ can also provide robust monitoring of nursing activity, offer opportunity for transparency of activity, feed into healthcare organizations’ key performance indicators and provide reassurance about the nature and quality of nurses’ work.